Plan de mejora para fortalecer el clima organizacional. Caso de estudio Cooperativa de Ahorro y Crédito Andina LTDA. - Mena Taco, Karla Vanessa (2020)
The purpose of this degree work, is to design an improvement plan that will strengthen the organizational climate of the Cooperativa de Ahorro y Crédito Andina Ltda. For this, it is necessary to theoretically base the organizational climate and its dimensions as a basis for this research, to diagnose the current situation and finally develop an improvement plan that strengthens the organizational climate of the same, based on the results previously obtained. The method of scientific observation used is the deductive, because part of validity proven theories, under a qualitative approach, using participatory action research design, through the application of a questionnaire that considers nine dimensions: leadership, sense of belonging, motivation, availability of resources, stability, communication, organizational structure, teamwork and collective values. Concluding that the climate is perceived in the cooperative is a participatory consultative; however, there is evidence of a low level of work motivation with an appreciation regular, and with the lowest grade in the category of good, dimensions: sense of belonging and stability; in addition, some of the collaborators consider that there is leakage or distortion in the information communicated; consequently, an improvement plan containing intervention and reinforcement activities is proposed, according to the motivation theories and the results extracted